If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5w+12=8w-3
We move all terms to the left:
5w+12-(8w-3)=0
We get rid of parentheses
5w-8w+3+12=0
We add all the numbers together, and all the variables
-3w+15=0
We move all terms containing w to the left, all other terms to the right
-3w=-15
w=-15/-3
w=+5
| x×(x-5)=134 | | -7/3+1/2u=-8/5 | | 4(x-6)-4x=-3(×+9)+3 | | 6y-5=2y+13 | | 4=-9+u | | 7x+2(-11x+1)=-2(4x-11)+15 | | 4x-6x=5 | | 289=216-u | | -14=-7/5v | | 4(2x+5)-17=0 | | 4(2x-8)+6(5x-2)+7=38x-36 | | 4v-8=64 | | 10y-13=3y=15 | | v-4=6 | | 2x+3(4x-3)=3(5x-2)-1 | | 228=15-u | | X-20=0.85x | | -5/3y=20 | | 17y+8=20y-4 | | 4+1x=3x+6 | | 2a+(2a-6)=34 | | 12x/4=1 | | 12x/412=1 | | 100−2x=80 | | 2x-9=(8-3x) | | 2^y+5=9 | | 2(37.5-y)+2y=75 | | 12x/4-48/4+93/3=-1 | | 3z+25=2z+15 | | 12x/4-48/4+93/3+1=1 | | 69.723=(x/100)(69.9256)+(100-x)/100)(70.9247 | | 18x+6=13x-9 |